The complete chloroplast genome of Damnacanthus indicus C.F.Gaertn. (Rubiaceae) - Lou, Shu-Mao (Mitochondrial DNA B Resour, 2021)
Damnacanthus indicus C.F.Gaertn. is an understorey shrub widely distributed in East Asia. In this study, the complete chloroplast genome of D. indicus was assembled and annotated. The chloroplast genome is 153,997 bp in total length, consisting of a large single-copy region (LSC 85,159 bp), a small single-copy region (SSC 17,584 bp) and two inverted repeat regions (25,627 bp for IRA and IRB,respectively). It contains 134 genes, including 89 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The phylogenetic analysis indicated that D. indicus is sister to Mitchella repens, suggesting a close relationship of the two genera.